Triggering receptor expressed on myeloid Cells-2 (TREM2) inhibits steroidogenesis in adrenocortical cell by macrophage-derived exosomes in lipopolysaccharide-induced septic shock. (5th April 2021) - Ye, Hui; Zhai, Qian; Fang, Ping; Yang, Shiyue; Sun, Yaqi; Wu, Shuijing; Huang, Ruoqiong; Chen, Qixing; Fang, Xiangming
Abstract: Purpose: Endogenously produced glucocorticoids exhibit immunomodulating properties and are of pivotal importance for sepsis outcome. Uncontrolled activation of the immune-adrenal crosstalk increases the risk of sepsis-related death. Triggering receptor expressed on myeloid cells-2 (TREM2) is richly expressed on macrophages and has been demonstrated to improve outcome of sepsis by enhancing elimination of pathogens. However, the role and mode of action of macrophage TREM2 on adrenocortical steroidogenesis remains unclear in septic shock. Methods: The acute septic shock model was established by intraperitoneally challenging wild-type (WT) and TREM2 knock-out ( Trem2 −/− ) mice with lipopolysaccharide (LPS, 30 mg/kg). The mice were assessed for TREM2 expression and local inflammation in adrenal gland and for synthesis of corticotropin releasing hormone (CRH) and adrenocorticotropic hormone (ACTH) in vivo. Bone marrow-derived macrophages or macrophage-derived exosomes were isolated from WT and Trem2 −/− mice and were co-cultured with adrenocortical cells. The expression of steroidogenic enzymes and corticosterone production was assessed. Results: Genetic deficiency of TREM2 caused significantly higher corticosterone levels at the early stage of LPS-induced septic shock; whereas TREM2 deficiency neither increased CRH and ACTH nor exacerbated the inflammation in adrenocortical tissue during septic shock. Ex vivo study revealed that Trem2 −/− macrophages significantly promoted the expression of steroidogenic enzymes and increased production of corticosterone. Furthermore, Trem2 −/− macrophage-derived exosomes were able to mimic Trem2 −/− macrophages in enhancing adrenocortical steroidogenesis. Conclusions: At the early stage of LPS-induced septic shock, corticosterone biosynthesis can be inhibited by macrophage TREM2 in adrenocortical cells, which might partially associate with macrophage-derived exosomes. Highlights: Deficiency of TREM2 elicits activation of adrenal glucocorticoid response in sepsis. Deficiency of TREM2 augments corticosterone biosynthesis in adrenocortical cells. Deficiency of TREM2 promoted steroid biosynthesis by macrophage-derived exosomes.